TRAF3IP3 promotes glioma progression through the ERK signaling pathway - Lin, Qi; Chen, Zhen; Shen, Zhao-Li; Xue, Fei; Qin, Jia-Jun; Kang, Xi-Peng; Chen, Zhong-Rong; Xia, Zhong -Yuan; Gao, Liang; Chen, Xian-Zhen (Frontiers in Oncology, 2022)
TRAF3IP3 was reportedly associated with poor prognosis in patients with melanoma; however, its role in glioma is unknown. We aimed to demonstrate the relationship between TRAF3IP3 and glioma and to investigate the potential role of TRAF3IP3 in glioma. Datasets were collected from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. We used the Wilcoxon rank-sum test to compared TRAF3IP3 expression in normal and glioma tissues. Kaplan–Meier analysis was performed to evaluate the correlation between TRAF3IP3 and patient survival rate. Gene set enrichment analysis (GSEA) was used to annotate the biological function of TRAF3IP3 in glioma. We also examined the effects of TRAF3IP3 on glioma progression, including characteristics such as cell proliferation, migration, and invasion, using cell proliferation, wound healing, and Transwell assays, respectively, paired with in vitro glioma cell lines and in vivo mouse xenograft models to determine the molecular mechanisms underlying these effects. High TRAF3IP3 expression in glioma tissues was associated with patients with neoplasm cancer tissue source site, and poorer overall survival (OS) (p = 0.03), which was validated using TCGA. GSEA revealed the enrichment of neuroactive ligand–receptor interactions, the olfactory pathway, proteasome pathway, cytokine–cytokine receptor interactions, and calcium signaling pathway in the TRAF3IP3 high-expression phenotype. TRAF3IP3 knockdown markedly suppressed the proliferation, migration, and invasion abilities of U251 glioma cells, whereas TRAF3IP3 overexpression notably promoted the progression of U118 cell tumors. Mechanistic studies revealed that TRAF3IP3 upregulated p-ERK expression in glioma cells. Notably, the ERK signaling pathway inhibitor U0126 drastically attenuated the effects of TRAF3IP3 on p-ERK and markedly blocked its tumor-promoting activity. TRAF3IP3 overexpression also promoted in vivo tumor growth in a nude mouse xenograft model. Collectively, TRAF3IP3 stimulates glioma cell proliferation, migration, and invasion, at least partly by activating the ERK signaling pathway. We hypothesize that TRAF3IP3 may participate in glioma development via the ERK signaling pathway and that elevated TRAF3IP3 expression may serve as a potential biomarker for glioma prognosis.